2017
DOI: 10.1111/ans.14039
|View full text |Cite
|
Sign up to set email alerts
|

Age 80 years and over is not associated with increased morbidity and mortality following pancreaticoduodenectomy

Abstract: No significant differences were seen in the rate of complications following PD in patients aged 80 or over compared to younger patients, although there appears to be a shorter survival in the elderly patients treated for pancreatic cancer. Careful selection of elderly patients and optimal peri-operative care, rather than age should be used to determine whether surgical intervention is indicated in this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
2
21
0
1
Order By: Relevance
“…A systematic review showed that patients aged 80 years or older were 1.5 fold more likely to have a complication than their younger counterparts [23]. However, with regard to complications including POPF and operative factors, we found no differences between the groups, which is in line with ndings reported in other published studies [21,24,25]. Our experience shows that PD can be performed safely in elderly patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A systematic review showed that patients aged 80 years or older were 1.5 fold more likely to have a complication than their younger counterparts [23]. However, with regard to complications including POPF and operative factors, we found no differences between the groups, which is in line with ndings reported in other published studies [21,24,25]. Our experience shows that PD can be performed safely in elderly patients.…”
Section: Discussionsupporting
confidence: 91%
“…In several studies, the length of hospital stay was not different between the elderly and younger groups [24,27,28]. It should be noted that elderly patients were far more likely than younger patients to be discharged to a rehabilitation facility instead of home [29,30].…”
Section: Discussionmentioning
confidence: 95%
“…It considered to the treatment for the periampullary cancer. Some reports revealed that PD was safe and feasible for the older patients in the aspect of short-term outcomes [23789]. However, there were some debates about whether PD had a survival benefit at long-term postoperative periods taking a high rate of postoperative complications.…”
Section: Introductionmentioning
confidence: 99%
“…The overall postoperative complication rate was high (OR 1.51, 95% CI 1.25-1.83, P < 0.001) in aged patients [70]. Another recent prospective study including 165 patients who had pancreaticoduodenectomy showed that the 90-day mortality rate (5.9% in those ≥ 80 years old vs. 2% in the younger group, P = 0.335) and the postoperative complication rate (64.7% in the elderly vs. 62.8% in the younger group, P = 0.83) were similar, although the older patients were far more likely to be discharged to a rehabilitation facility than younger patients were (47.1% vs. 12.8%, P < 0.001) [71]. Careful selection of elderly patients and optimal periopera-tive care, rather than age, should be used to determine whether surgical intervention is indicated.…”
Section: Anesthesia In Elderly Patientsmentioning
confidence: 86%